Prevalence and risk factors of mastitis in dairy cows (Bangladesh Veterinarian, 2010)
Identification of risk factors is important for the design of control programmes for mastitis in cows. Information about farms and management was collected at a farm visit. California Mastitis Test (CMT) was performed to assess sub-clinical mastitis, and cows, udder and milk were examined for clinical mastitis. A total of 347 lactating cows from 83 farms in the dry season (November - February) and 388 lactating cows from 89 farms in the wet season (June - October) were studied. The overall prevalence of mastitis was 19.9% and 44.8% in dry and wet seasons, respectively. The prevalence of mild mastitis was 17.3% and 40.7%, whereas that of moderate mastitis was 2.6% and 4.1% in dry and wet seasons, respectively. The prevalence of mastitis was higher (P